Intraoperative virtual reality for older patients undergoing total knee arthroplasty: study protocol for a randomized clinical trial - Juan P. Espinosa-Leon; Ryan Mathura; Guanqing Chen; Melisa Joseph; Trishna Sadhwani; Najla Beydoun; Edjay R. Hernandez; Tyler Riley; Lisa J. Kunze; Valerie Goodspeed; Brian P. O’Gara (Trials)
Abstract Background In an aging surgical patient population, preventing complications such as oversedation has taken increasing priority in perioperative care. Intraoperative use of virtual reality (VR) may decrease sedative requirements. We hypothesize that the use of immersive VR during total knee arthroplasty (TKA) will lead to decreased propofol requirements, improved patient-reported satisfaction, and reduced postoperative opioid requirements compared to active and usual care controls. Methods This is a single-center, randomized clinical trial of older (age > 60) patients undergoing TKA. Participants will be randomized into three groups (2:2:1): VR immersion, music, and sham VR plus usual care. All patients will receive a regional block and spinal anesthesia. Patients in the immersive VR and music groups will use patient-controlled sedation (PCS) with propofol, while those in the sham VR group will act as the standard of care control group and will receive monitored anesthesia care (MAC) with propofol infusion. Statistical analysis Analyses will be conducted using IBM SPSS Statistics Version 25, considering a two-sided p-value < 0.05 to be statistically significant. The primary outcome is the intraoperative dose of propofol (mg kg−1 min−1). Secondary outcomes include patient satisfaction, post-anesthesia care unit (PACU) length of stay, postoperative pain scores and analgesic requirements, functional outcomes, postoperative delirium, and postoperative neurocognition. Discussion VR used as a non-pharmacological adjunct to regional and spinal anesthesia during TKA may reduce sedative requirements while maintaining patient satisfaction. If true, this approach to minimizing sedation may impact clinical outcomes including perioperative complications and length of stay for older patients, while maintaining a high degree of patient satisfaction. Trial registration This trial was registered on ClinicalTrials.gov on January 29, 2021. The registration number is NCT04748549.